Perubahan Sikap Keamanan Pangan Siswa Berdasarkan Persepsi Orang Tua dan Anak - Winiati Pudji Rahayu; Siti Nurulfalah; Ruki Fanaike (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2015)
Food safety program in school is one of effort to keep children from the risk of consuming unsafety foods. Food safety programs that applied in school were posting food safety poster, conducting food safety extension, establishing food safety team, operating food safety car, and accessing klubpompi websites. This research was aim to gain knowledge of school chlidren’s attitude alteration after receiving food safety program and parents support in food safety program in school. The survey was conducted to 397 children and 195 parents, and the results were processed by SPSS program using correlation and contingency analysis. The survey results showed the activities that give significant effect to attitude alteration of school children in the West part of Indonesia were adhering poster and establishing food safety team in school. Meanwhile posting food safety poster and conducting food safety extension in school have given significant effect in the East part of Indonesia. Attitude alteration of school children to buy food at school canteen than at food vendors outside school canteen is in high category in the West part of Indonesia (66%) and very high in the East part of Indonesia (94%).